Vaccine induced mucosal and systemic memory NK/ILCs elicit decreased risk of SIV/SHIV acquisition - Rahman, Mohammad Arif; Silva de Castro, Isabela; Schifanella, Luca; Bissa, Massimiliano; Franchini, Genoveffa (Frontiers in Immunology, 2024)
SIV and HIV-based envelope V1-deleted (ΔV1) vaccines, delivered systemically by the DNA/ALVAC/gp120 platform, decrease the risk of mucosal SIV or SHIV acquisition better than V1-replete vaccines. Here we investigated the induction of mucosal and systemic memory-like NK cells as well as antigen-reactive ILC response by DNA/ALVAC/gp120-based vaccination and their role against SIV/SHIV infection. ΔV1 HIV vaccination elicited a higher level of mucosal TNF-a + and CD107 + memory-like NK cells than V1-replete vaccination, suggesting immunogen dependence. Mucosal memory-like NK cells, systemic Granzyme B + memory NK cells, and vaccine-induced mucosal envelop antigen-reactive IL-17 + NKp44 + ILCs, IL-17 + ILC3s, and IL-13 + ILC2 subsets were linked to a lower risk of virus acquisition. Additionally, mucosal memorylike NK cells and mucosal env-reactive IFN-g + ILC1s and env-reactive IL-13 + ILC2 subsets correlated with viral load control. We further observed a positive correlation between postvaccination systemic and mucosal memory-like NK cells, suggesting vaccination enhances the presence of these cells in both compartments. Mucosal and systemic memory-like NK cells positively correlated with V2-specific ADCC responses, a reproducible correlate of reduced risk of SIV/HIV infection. In contrast, an increased risk was associated with the level of mucosal PMA/Ionomycin-induced IFN-g + and CD107 + NKG2A -NKp44 -ILCs. Plasma proteomic analyses demonstrated that suppression of mucosal memory-like NK cells was linked to the level of CCL-19, LT-a, TNFSF-12, and IL-15, suppression of systemic env-reactive Granzyme B + memory-like NK cells was associated with the level of OLR1, CCL3, and OSM, and suppression of IL-17 + ILCs immunity was correlated with the level of IL-6 and CXCL-9. In contrast, FLT3 ligand was associated with promotion of protective mucosal env-reactive IL-17 + responses. These findings emphasize the importance of mucosal memory-like NK cell and envelope-reactive ILC responses for protection against mucosal SIV/SHIV acquisition.